New generation of dictionaries of the Karaim language by Karaim speakers - Rinkevičius, Šarūnas (Vilnius University Proceedings, 2024)
The paper aims at providing an assessment of the new generation of dictionaries of the Karaim language prepared and published by Karaim speakers over the last two decades. Apart from that, the paper aims at providing a brief analysis of the already existing documentation of the Karaim language. The article is divided into two parts: firstly, the evaluation of the previously published dictionaries of Karaim language is provided; secondly, the new generation of dictionaries published by Karaim speakers, is being analysed, focussing on four works, namely two Polish-Karaim, one Russian-Karaim and one Lithuanian-Karaim dictionary. The dictionaries are being analysed by raising the same question in each case: what information in these dictionaries is provided about the Karaim language?